Effect of Nebulized Amphotericin B in Critically ill Patients With Respiratory Candida spp. De-colonization: A Retrospective Analysis - Du, Hangxiang; Wei, Limin; Li, Wenzhe; Huang, Bixia; Liu, Yongan; Ye, Xiaofei; Zhang, Sheng; Wang, Tao; Chen, Yizhu; Chen, Dechang; Liu, Jiao (Frontiers in Medicine, 2021)
The potential relationship among airway Candida spp. de-colonization, nebulised amphotericin B (NAB), and occurrence of ventilator-associated pneumonia (VAP) in patients who are critically ill has not been fully investigated, especially concerning effects on survival. In this observational, retrospective, corhort study, we included patients aged >18 years who required mechanical ventilation (MV) for >48 h, with at least two consecutive positive Candida spp. test results. Patients were categorized into NAB and no NAB (control) groups. Propensity matching , multiple Cox proportional hazard model and multivariate analyses were performed. Throughout an 8-year study period, 526 patients had received MV and had positive respiratory tract Candida spp. cultures. We included 275 patients and excluded 251 patients. In total, we successfully matched 110 patients from the two groups (each group, n = 55). The Candida spp. de-colonization rate was 69.1% in patients treated with NAB. VAP incidence did not differ significantly between the NAB (10.91%) and control (16.36%) groups (P = 0.405). Pseudomonas aeruginosa-related VAP rates differed significantly between the NAB (10.91%) and control (25.45%) groups (P = 0.048). Five (9.1%) patients in the NAB group died during hospitalization compared with 17 (30.9%) controls (P = 0.014). At 28 days, 9 (16.4%) and 16 (29.1%) deaths occurred in the NAB and control groups, respectively, (P = 0.088). The cumulative 90-day mortality rate differed significantly between the two groups (23.6% vs. 43.6%, P = 0.015). Multivariate logistic regression analyses indicated a decreased 90-day mortality in the NAB group (adjusted odds ratio 0.413; 95% CI 0.210–0.812; P = 0.01). In subgroup analyses, the NAB-associated decreased risk of death at 90 days was consistent across subgroups of patients with a Candida score of 2, younger age (<64 years), a higher APACHE II score (≥25), fewer Candida sites (<2), or MV at admission. NAB treatment contributed to Candida spp. airway de-colonization, was associated with a reduced risk of P. aeruginosa-related VAP, and improved 90-day mortality in patients critically ill with Candida spp. tracheobronchial colonization who had received MV for >2 days. NAB may be an alternative treatment option for critically ill patients with VAP.